Analysis of Business Process Reengineering and Export Platform in Supporting Business Exports of Creative Economy Players in the Micro, Small and Medium Business in Culinary Sub-sector - Sugeng Santoso; Arfeo Natanael; Ariela Griselda; Jeshica Khoirunnisa; Martua Simanjuntak; A.A. Raka Bagus; Liz Zeny Merry (Journal of Economics, Business, and Government Challenges, 2021)
The creative economy has a large contribution to Gross Domestic Product (GDP) that the role of creativity and knowledge in generating new ideas is a driver of economic growth and is able to absorb a large number of workers. Strong infrastructure support is needed, such as platfroms and facilitators as an intermediary between creative industry players and the market or consumer if they want to expand their business into the global market. The purpose of this research is to describe the factors that can help Indonesian creative industry players to enter the global market by focusing on four things: Business Process Reengineering ; support system (in terms of product technology, legality, and capital); as well as a platform as an infrastructure as an intermediary between creative industry players and the global market. This research used a qualitative method (review paper) by using data obtained from related journals and articles that were studied, then described descriptively based on the researcher’s perspective. The key informants in the study were cassava flour producers and gluten free food pioneers who have successfully exported as research subjects